Thermographic and histopathological study of the effects of plasma jet therapy upon dermis repair in rat: Thermographic and histopathological study of the effects of plasma jet therapy upon tissue repair - Cerqueira, Carla Barreto Silva de; de Souza, Paulo Badaró; Marchionni, Antônio Márcio Teixeira; Almeida, Mylana; Medrado, Alena Peixoto; Matos, Josilene Borges Torres Lima (Revista de Ciências Médicas e Biológicas, 2024)
Background: Biomodulatory therapies have been used to improve the healing pattern and assist in tissue repair. The plasma jet is a therapy that has been currently indicated for dermatological use and aesthetic purposes. This study aimed to evaluate the effects of plasma jet on the repair of skin wounds in rats through thermographic imaging and histopathological analysis. Methodology : 20 Wistar rats were divided into a control group (CG) and plasma jet group (PJG). A cutaneous surgical wound was performed on the back of the animals, and thermographic recording was performed at different periods. Only the PJG was submitted to plasma jet therapy immediately after the surgery and in the following two days. Half of the animals in each group were sacrificed on the fifth day, after the surgical procedure, and another half on the tenth day. A tissue sample from the animals was removed and processed for histological analysis. Results: Thermograms showed greater variation in the thermal coefficient in the PJG, especially on the fifth day (p>0.05). These results confirm the histological findings in this period that exhibited greater collagen biosynthesis in the dermis (p<0.05). Conclusion: Plasma jet treatment promoted an improvement in the collagen fibers pattern, and the use of Infrared Thermography was useful for monitoring tissue repair.